(untitled) (Journal of Environmental Science and Natural Resources, 2016)
Morphometric and meristic characters and truss measurements of 32 Monopterus cuchia, and of 17 Ophisternon bengalense were compared to know the population status of two fresh water eels of Bangladesh. The mean numbers of line below head were significantly different between two species. Significant differences were observed in 11 morphometric characters: Pre dorsal length (PDL), Post dorsal length (PoDL), Post anal length (PoAL), Head length (HL), Snout length (SnL), Upper jaw length (UJL), Lower jaw length (LJL), Head width (HW), Pre orbital length (PrOrL), Least body diameter (LBD) and Highest body diameter (HBD) and one truss measurement (3-5) between two species in varying degrees. For both morphometric and landmark measurements, the first and second DF (discriminant function) accounted 64.8% and 33.2% of among group variability, explaining 98% of total group variability. M. cuchia collected from Mymensingh and from Dinajpur constructed one sub-cluster and O. bengalense collected from Sathkhira and from Bagerhat constructed another sub-cluster based on the Distance of squared Euclidean dissimilarity. A correct classification of individuals into their original population from leave-one-out-classification varied between 93.3% and 94.1% by discriminant analysis. The results of the present study suggested that there was limited intermingling among populations and the populations of the species were separated from one another. J. Environ. Sci. & Natural Resources, 9(1): 139-141 2016